Knowledge Gaps in Understanding the Etiology of Anemia in Indonesian Adolescents. Issue 1 (June 2021) - van Zutphen, Kesso Gabrielle; Kraemer, Klaus; Melse-Boonstra, Alida
Background: Anemia is a public health problem among adolescents in Indonesia. Strategies to prevent or treat anemia should be tailored to local conditions, taking into account its specific etiology and prevalence in a given setting and population group. Objective: This review aims to (1) identify and synthesize the current knowledge on the etiology of anemia among adolescents in Indonesia, (2) reveal knowledge gaps in this area, and (3) suggest directions for future research and programmatic work. Methods: We systematically searched PubMed, Web of Science, Scopus, Medline, and WorldCat databases for peer-reviewed journal articles to identify which etiological factors were related to anemia among Indonesian adolescents. Research papers were reviewed and included in the review according to inclusion criteria. Results: Of 13 studies, 8 showed that anemia was associated with iron deficiency; 4 are suggestive of vitamin A deficiency; and 2 of folic acid deficiency. Five studies underscore different etiological determinants for anemia, such as malaria, protein and energy malnutrition, vitamin B2 deficiency, calcium, and vitamin C deficiency. Based on these findings, we developed a framework on knowledge gaps on the etiology of anemia among adolescents in Indonesia, divided in 3 levels of knowledge: (1) significant knowledge gaps, (2) knowledge gaps, and (3) established knowledge. Conclusions: The knowledge gaps around the etiology of anemia among Indonesian adolescents are significant. Our framework emphasizes the need for further research across all etiological factors, namely inadequate nutritional intake and absorption, genetic hemoglobin disorders, infection and inflammation, and menstrual disorders.